The Death of the Author and Anticolonial Thought - Griffiths, Michael R. author. (orcid)0000-0002-7501-906X Link aut Link
IX, 106 p. 1 illus.
Keywords: “This highly original and thought-provoking study demands that we reconsider the idea of the death of the author from the point of view of some of its sharpest critics from the formerly colonized world. It will permanently change the way we think about authorship and the legacy of empire.” —Anna Bernard, author of Decolonizing Literature "This rich text offers a much-needed reflection on the relation between anticolonial thought and Barthes’ fabled death of the author. Griffiths’ rigorous analyses of literary intention and community in the works of Fanon, Glissant, and Said will doubtlessly stimulate future engagements with these thinkers by experts and students alike." —David Ventura, Department of Philosophy, Newcastle University, UK The Death of the Author and Anticolonial Thought promises to transform a decades old debate in literary studies about the relation between structure and agency, form and intention by giving a detailed account—previously unstudied—of the way colonized writers have responded to, learned from, and critiqued the death of the author postulate declared by Roland Barthes in 1967. The book is a cultural history of these debates—with a particular focus on two crucial two key case studies, Martinican poet and thinker Édouard Glissant and Palestinian literary and cultural critic Edward Said, this book, then, examines the immediate emergence and intensification of such responses to the postulate of the author’s deathly absence from the text, in order to suggest that metropolitan literary theory drew both critique and engagement from scholars of black, decolonial and Global South background from both before 1967 and Barthes’s declaration and in its wake. This book provides a focused account of the early history of the way global literatures have engaged with, critiqued, and occasionally adopted the lessons and limitations of the poststructuralist critique of that most fetishised and also reviled of figures: the author. Michael Griffiths is Senior Lecturer in English Literatures at the University of Wollongong, Australia. He is the author of The Distribution of Settlement: Appropriation and Refusal in Australian Literature and Culture (2018). His essays have appeared in Textual Practice, Discourse, Postcolonial Studies, Australian Humanities Review and many edited books.